Game-Model-Based Network Security Risk Control. - Ni, Zhen; Li, Qianmu; Liu, Gang (Computer (00189162), 2018)
Network security decisions must consider how to balance information security risk and output in light of limited resources. Using game theory, the authors propose an optimum attack-defense decision-making algorithm that considers the interaction between attackers and defenders.